The implementation of a Merit System in the Selection of Village Officers in the Indonesian Region of Yogyakarta (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2020)
This article aims to examine the selection mechanism for village officials in the Indonesian Distinctive Region of Yogyakarta. This article will focus on the problem of the differences in the selection mechanism for village officials in Yogyakarta, particularly in Kulon Progo, Sleman, Bantul, and Gunung Kidul Districts. In this study, researchers use the theory of merit system, which means a system working based on competency performance and professionalism, which is open and provides opportunities and supports every employee to develop the best performance for the organization, which is a manifestation of change as well as coaching for every employee to create productivity and competence (Meyrina, 2016). The data are collected from four districts in Yogyakarta by series of observations to the implementation of regional regulations. The data are categorized and analyzed. This study concludes that the implementation of the merit system in the four districts is through open selection, which in practice has differences in the examination mechanism. This shows that in the application of the merit system there are variations from the four districts. Besides, another difference is the neutrality of the selection committee, which has different mechanisms between districts. One of them is collaborating with universities and third parties. This was done to maintain the neutrality of the committee and to create professional, competent, and high integrity of human resources.